2017
DOI: 10.3389/fmolb.2017.00066
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric RNA Distribution among Cells and Their Secreted Exosomes: Biomedical Meaning and Considerations on Diagnostic Applications

Abstract: Over the past few years, exosomes and their RNA cargo have been extensively studied because of the fascinating biological roles they play in cell-to-cell communication, including the signal exchange among cancer, stromal, and immune cells, leading to modifications of tumor microenvironment. RNAs, especially miRNAs, stored within exosomes, seem to be among the main determinants of such signaling: their sorting into exosomes appears to be cell-specific and related to cellular physiopathology. Accordingly, the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 153 publications
(183 reference statements)
2
30
0
Order By: Relevance
“…The mechanisms for differential enrichment of particular miRNAs into ADEVs following ATP, TNFα, or IL-1β are less clear. Previous studies have reported differential sorting of miRNA into EVs 43 , and several mechanisms for miRNA loading into EVs including lipid-mediated RNA loading, RNA-binding protein-assisted RNA loading, loading by non-templated 3′-end uridylation of microRNAs 44 46 . However, mechanisms regulating stimulus-dependent inclusion/exclusion of particular miRNA cargo are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms for differential enrichment of particular miRNAs into ADEVs following ATP, TNFα, or IL-1β are less clear. Previous studies have reported differential sorting of miRNA into EVs 43 , and several mechanisms for miRNA loading into EVs including lipid-mediated RNA loading, RNA-binding protein-assisted RNA loading, loading by non-templated 3′-end uridylation of microRNAs 44 46 . However, mechanisms regulating stimulus-dependent inclusion/exclusion of particular miRNA cargo are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This opposite deregulation would suggest that the oncogenic function of UCA1 is crucial for tumor progression, inducing tumor cells to retain the lncRNA by limiting its secretion through exosomes. 58 …”
Section: Discussionmentioning
confidence: 99%
“…Cell stressors not only promote the release of EVs, but more importantly, also promote highly specific EV-containing microRNAs (miRNAs; Gray et al, 2015 ; Lee et al, 2016 , 2017 ). Accumulating evidence indicates that a specific repertoire of miRNAs is actively selected and loaded into EVs ( Skog et al, 2008 ; Xu et al, 2013 ; Momose et al, 2016 ; Ragusa et al, 2017 ). This process involves an ATP-dependent, active sorting mechanism ( Xu et al, 2013 ) and involves RNA-binding proteins that are enriched in EVs ( Laffont et al, 2013 ; Villarroya-Beltri et al, 2013 ; Cha et al, 2015 ; McKenzie et al, 2016 ; Santangelo et al, 2016 ; Shurtleff et al, 2016 ; Teng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%